Laboratório do ensino de matemática: a (re)construção de materiais didáticos para ensinar geometria nos anos finais do ensino fundamental - Ciqueira, Gutembergue Narciso (Universidade Federal do Tocantins, 2025)
This monograph presents the results of an observation carried out during classes in the curricular component Laboratório de Ensino de Matemática I, of the Mathematics Degree course at UFT-Arraias, in the academic semester 2023/2. The research was conducted in the Laboratório de Ensino de Matemática (LEM) of the same institution. The focus of the observation was the actions of the academics enrolled in the discipline, during the planning, creation and development of lesson plans aimed at teaching Geometry to male and female students in the final years of Elementary School. During the preparation of lesson plans, students learned about effective methods for teaching Mathematics. Using these methods, they were able to create teaching strategies using manipulative teaching resources and educational technologies. At the end of the work developed at LEM, it was evident that, in addition to becoming familiar with teaching methodologies, the academics expanded their specific knowledge in Mathematics by recognizing properties of Geometry that were previously not fully clear to them. It was noticeable that the lesson plans, created by the academics enrolled in the subject, in addition to benefiting their learning, can facilitate the work of the basic education teacher in the classroom. Diversified approaches to teaching Geometry, developed and improved with the use of educational technologies, provide more enjoyable learning. The alternatives created by academics, presented in the body of this monograph, which bring methodological diversity, can make the content more accessible and understandable for students, a situation that can be interpreted as significant learning for teaching.